The sectoral systemic risk buffer: General issues and application to residential real estate-related risks - Markus Behn; Daniel Abreu; Francesco Ciampi; Federica Ciocchetta; Wanda Cornacchia; Marija Drenkovska; Marco Forletta; Benedikt Fritz; Sebastian Geiger; Barbara Jarmulska; Mariya Melnychuk; Steffen G. Meusel; et al. (European Central Bank (ECB), 2024)
The 2019 revision to the Capital Requirements Directive allowed the systemic risk buffer to be applied on a sectoral basis in the European Union. Since then an increasing number of countries have implemented the new tool, primarily to address vulnerabilities in the residential real estate sector. To inform and foster a consistent understanding and application of the buffer, this paper proposes two specific methodologies. First, an indicator-based approach which provides an aggregate measure of cyclical vulnerabilities in the residential real estate sector and can signal a potential need to activate a sectoral buffer to address them. Second, a modelbased approach following a stress test rationale simulating mortgage loan losses under adverse conditions, which can be used as a starting point for calibrating a sectoral buffer. Besides these methodological contributions, the paper conceptually discusses the interaction between the sectoral buffer and other prudential requirements and instruments, ex ante and ex post policy impact assessment, and factors guiding the possible release of the buffer. Finally, the paper considers possible future applications of sectoral buffer requirements for other types of sectoral vulnerabilities, for example in relation to commercial real estate, exposures to nonfinancial corporations or climate-related risks.
Keywords: G21; G28; 330; financial stability; banks; macroprudential policy; capital buffers